Kedudukan Peraturan Desa Dalam Hierarki Perundang-undangan Setelah Keluarnya Undang-Undang Nomor 12 Tahun 2011 - Imelda sapitri; Deni Jaya Saputra (Universitas Islam Negeri sultan syarif kasim Riau, 2020)
This article is about position of village regulation in hierarchy of legislation laws after coming the law number 12 of 2011 about village regulation based on law number 10 of 2004 stated that one of the regulation in law hierarchy as long as in section 7 verse (2). Moreover, after coming the law number 12 of 2011 that changed the law number 10 of 2004 village regulation is not appear in hierarchy but still effect as in section 101 said that: “all of laws is the implication of law number 10 of 2004, it was stated that effect as long as incompatible with this law regulation”. Village regulation is also get attribution of authority law number 6 of 2014 about village. Therefore, it is clear that status of village regulation is law legislation which have the power of laws. In this autonomy, the village is given the authority to organize and manage its own so that the village regulation become important to implement the authority that to be more effective.Keywords: Village Regulation, Village Representative Board, and Hierarchy